Different brain profiles in children with prenatal alcohol exposure with or without early adverse exposures. Issue 15 (13th July 2020) - Andre, Quinn R.; McMorris, Carly A.; Kar, Preeti; Ritter, Chantel; Gibbard, W. Ben; Tortorelli, Christina; Lebel, Catherine
Abstract: Prenatal alcohol exposure (PAE) can alter brain development and impact mental health outcomes, and often occurs in conjunction with postnatal adversity (e.g., maltreatment). However, it is unclear how postnatal adverse exposures may moderate mental health and brain outcomes in children with PAE. T1‐weighted and diffusion magnetic resonance imaging were obtained from 66 participants aged 7–16 years. Twenty‐one participants had PAE and adverse postnatal exposures (PAE+), 12 had PAE without adverse postnatal exposures (PAE−), and 33 were age‐ and gender‐matched controls unexposed to either prenatal alcohol or postnatal adversity. Internalizing and externalizing mental health symptoms were assessed using the Behavioral Assessment System for Children II, Parent‐Rating Scale. ANCOVAs were used to compare mental health symptoms, limbic and prefrontal cortical volumes, and diffusion parameters of cortico‐limbic white matter tracts between groups, and to assess brain‐mental health relationships. Both PAE groups had worse externalizing behavior (higher scores) than controls. The PAE− group had lower fractional anisotropy (FA) in the bilateral cingulum and left uncinate fasciculus, and smaller volumes in the left anterior cingulate cortex than controls and the PAE+ group. The PAE− group also had higher mean diffusivity (MD) in the left uncinate than the PAE+ group, and smaller right anterior cingulate and superior frontal gyrus volumes than controls. These findings show different brain structure and mental health symptom profiles in children with PAE with and without postnatal adversity, highlighting the need to consider adverse postnatal exposures in individuals with PAE. Abstract : We compared mental health symptoms, brain volumes, and diffusion parameters in 21 participants with PAE and adverse postnatal exposures (PAE+), 12 with PAE without adverse postnatal exposures (PAE−), and 33 age‐ and gender‐matched unexposed controls. Both PAE groups had worse externalizing behaviour than controls. The PAE− group had lower fractional anisotropy (FA), higher mean diffusivity, and smaller volumes in several areas compared to controls and the PAE+ group. These findings show different brain structure and mental health profiles in children with PAE with and without postnatal adversity, highlighting the need to consider adverse postnatal exposures in individuals with PAE.